MARRIAGE FOR COVERING DISGRACE: The Practice of Kawi' Pura Tradition in the East Kolaka Muslim Society - Darlis, Syamsul (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
According to the Indonesian Compilation of Islamic Law (KHI), unmarried pregnant women may only be married to the men who impregnated them. However, this rule is frequently disregarded by the Kolaka Muslim society. They typically opt for kawi' pura tradition to tackle the case, which is to marry the pregnant woman to another man. This marriage is followed by a contract stipulating an immediate divorce. Its purpose is to conceal shame or disgrace. This article seeks to investigate the rationale behind the practice of kawi' pura. Data were collected through observation and interviews and then analyzed qualitatively. This article finds that the implementation of the tradition is driven by four factors: the pressure to cover up family disgrace, adherence to ancestral traditions, lack of awareness of marriage law, and low levels of public education. Normatively, this practice is not justified by Islamic law. In state law, this practice is not clearly regulated or prohibited; however, it contradicts the principle of the Marriage Law either according to the Compilation or Islamic marriage law in general.[Menurut Kompilasi Hukum Islam Indonesia (KHI), wanita hamil yang belum menikah hanya boleh dinikahkan dengan pria yang menghamilinya. Namun, aturan ini sering diabaikan oleh sebagian orang Kolaka. Mereka biasanya memilih tradisi kawi' pura untuk menangani kasus ini, yaitu mengawinkan wanita hamil dengan pria lain. Perkawinan ini diikuti dengan perjanjian perkawinan yang menetapkan perceraian langsung, karena tujuan utamanya adalah untuk menutupi aib. Artikel ini berusaha menyelidiki alasan di balik praktik kawi' pura. Data dikumpulkan melalui observasi dan wawancara, kemudian diinterpretasikan secara kualitatif. Setelah melakukan penelitian lapangan, artikel ini menemukan bahwa pelaksanaan tradisi ini didorong oleh empat faktor: tekanan untuk menutupi aib, kepatuhan terhadap tradisi leluhur, kurangnya kesadaran tentang hukum perkawinan nasional, dan rendahnya tingkat pendidikan masyarakat. Secara normatif, praktik ini tidak dibenarkan oleh hukum Islam. Dalam hukum negara, praktik ini juga tidak diatur atau dilarang secara tegas, tetapi praktik ini kontras dengan asas perkawinan baik menurut Kompilasi Hukum Islam maupun Hukum Perkawinan Islam secara umum.]